Direct identification of neoantigen-specific TCRs from tumor specimens by high-throughput single-cell sequencing. Issue 7 (28th July 2021) - Lu, Yong-Chen; Zheng, Zhili; Lowery, Frank J; Gartner, Jared J; Prickett, Todd D; Robbins, Paul F; Rosenberg, Steven A
Abstract : Background: Recognition of neoantigens by T cells plays a major role in cancer immunotherapy. Identification of neoantigen-specific T-cell receptors (TCRs) has become a critical research tool for studying T cell-mediated responses after immunotherapy. In addition, neoantigen-specific TCRs can be used to modify the specificity of T cells for T cell-based therapies targeting tumor-specific mutations. Although several techniques have been developed to identify TCR sequences, these techniques still require a significant amount of labor, making them impractical in the clinical setting. Methods: Thanks to the availability of high-throughput single-cell sequencing, we developed a new process to isolate neoantigen-specific TCR sequences. This process included the isolation of tumor-infiltrating T cells from a tumor specimen and the stimulation of T cells by neoantigen-loaded dendritic cells, followed by single-cell sequencing for TCR and T-cell activation markers, interferon-γ and interleukin-2. Results: In this study, potential neoantigen-specific TCRs were isolated from three melanoma and three colorectal tumor specimens. These TCRs were then synthesized and transduced into autologous T cells, followed by testing the recognition of neoantigens. A total of 28 neoantigen-specific TCRs were identified by this process. If identical TCR sequences were detected from two or more single cells, this approach was highly reliable (100%, 19 out of 19 TCRs). Conclusion: This single-cell approach provides an efficient process to isolate antigen-specific TCRs for research and clinical applications.